ANALISIS TINGKAT EFISIENSI BANK PERSERO DAN BANK SWASTA NASIONAL DEVISA DI INDONESIA TAHUN 2005-2010: PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - , Ayu Ratnasari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research background aims to analyze the level of efficiency of state owned banks and foreign exchange commercial banks in Indonesia using Data Envelopment Analysis (DEA). The banking sector is the financial institution that carries out functions of intermediation which its efficiency level is judged through the ability in optimizing number of funds obtained from the public and then channeled to the economy actors who need it. This research uses DEA analysis tools. The Inputs are cost of labor, cost of funds, and cost of physical capital and outputs are credit given to any associated bank, credit given to third parties, and the securities owned by the bank. The result shows, efficiency level of the banks included in a group of national banks and national private foreign exchange bank in the 2005-2010 are diverse. Banks that are able to maintain the level of optimal efficiency during the period of research on a group of national banks are Bank Negara Indonesia, Bank Rakyat Indonesia and Bank Mandiri. Banks that are able to maintain the level of optimal efficiency during the period of research on a group of national private foreign exchange bank are Bank Bukopin, Bank Central Asia, Bank Sinarmas, and Bank Panin. On the other hand, the inefficient banks can improve its efficiency through become more efficient in cost of physical capital and still have a big chance to improve its private ownership of securities.